Biological activities of Prunella vulgaris extract - Psotová, Jitka; Kolár, Milan; Sousek, Jaromír; Svagera, Zdenek; Vicar, Jaroslav; Ulrichová, Jitka (Phytotherapy research, 2003)
The organic fraction (OF; 25.7% w/w of rosmarinic acid) of Prunella vulgaris (total extract) was found to exhibit the following: scavenging activity on diphenylpicrylhydrazyl radical (DPPH), inhibition of in vitro human LDL Cu(II)-mediated oxidation, protection of rat mitochondria and rat hepatocytes exposed to either tert-butyl hydroperoxide, or to Cu(II) and Fe(III) ions. OF also showed a potential to inhibit rat erythrocyte haemolysis and it reduced the production of LTB(4) in bovine PMNL generated by the 5-lipoxygenase pathway. Other observations included antiproliferative effects against HaCaT cells and mouse epidermal fibroblasts and a moderate OF antimicrobial activity on gram-positive bacteria. Rosmarinic, caffeic and 3-(3,4-dihydroxyphenyl)lactic acids exhibited less potent activity than the plant extract in all bioassays. The antioxidative, antimicrobial, together with antiviral effects offer good prospects for the medicinal applications of P. vulgaris.
Keywords: Mitochondria, Liver; jaterní mitochondrie; Animals; Free Radical Scavengers; Antioxidants; kationty; mikrobiální testy citlivosti; Rats, Wistar; Cell Line, Tumor; železo; rostlinné extrakty; Cations; hemolýza; fytogenní protinádorové látky; lidé; antiinfekční látky; Mice; Anti-Infective Agents; Phytotherapy; měď; myši; Copper; Antineoplastic Agents, Phytogenic; Picrates; grampozitivní bakterie; oxidace-redukce; pikráty; Microbial Sensitivity Tests; scavengery volných radikálů; fytoterapie; Male; Oxidation-Reduction; Iron; bifenylové sloučeniny; antioxidancia; Prunella; Hemolysis; krysa rodu Rattus; Plant Extracts; zvířata; mužské pohlaví; Biphenyl Compounds; Gram-Positive Bacteria; Rats; nádorové buněčné linie; potkani Wistar; Humans